Construction management competencies needed by block laying and concreting students at Rivers State Technical Colleges for enhancing entrepreneurship development - Igweagbara, Silverline Nkasiobi; Orji, Temple Chigozilem (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
This study looked at the construction management competencies needed by brick/block-laying and concreting students at Rivers State to enhance entrepreneurship. The study was based on two research questions and two hypotheses. The design of the study was based on a survey. The study population consisted of 15 Brick/block laying and Concreting teachers and the fifty builders registered with the Ministry of Works of Rivers State bringing the total population of the study to sixty-five persons. As the population is small, sampling was not conducted. Therefore, the entire population was utilized for the study. The study was conducted using a structured questionnaire to be responded to in a 5-point Likert scale. The questionnaire is titled Construction Management Competencies Needed of Brick / Block-Laying / Concreting Students for Enhancing Entrepreneurship. The validity of the tool was verified by three lecturers, belonging to the Department of Industrial and Technical Education at Ignatius Ajuru University of Education, who conducted a face and content validity on the questionnaire items. The reliability of the instrument was also verified by administering the instrument to fifteen teachers of block-laying and concreting in technical colleges in Akwa Ibom and contiguous States. The internal consistency of the instrument was determined by the Cronbach alpha reliability coefficient. Research questions were answered using mean and standard deviation while null hypotheses were tested by z-test at .05 levels of significance. The findings of this study showed that: Using CAD in drawing; using building information modeling; using self-healing concrete; working with fast hardening cement; offsite construction techniques; operating and using machines in construction; where time management skills required by brick/block-laying and concreting students for entrepreneurship at Rivers state technical collages.